Detection and remediation of organophosphorus compounds by oximate containing organogels1. Issue 10 (14th October 2015) - Hiscock, Jennifer R.; Sambrook, Mark R.; Wells, Neil J.; Gale, Philip A.
<x xml:space="preserve">Abstract</x> A series of supramolecular diamide organogels containing a reactive compound for the remediation of organophosphorus (OP) species, in particular OP chemical warfare agents (CWAs), has been prepared in DMSO.